The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2478/s11535-006-0020-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of powdery mildew (Erysiphe graminis sp. tritici) and take-all disease (Gaeumannomyces graminis sp. tritici) in wheat (Triticum aestivum L.) by means of leaf reflectance measurements

Abstract: Identification of powdery mildew (Erysiphe graminis sp. tritici ) and take-all disease (Gaeumannomyces graminis sp. tritici ) in wheat (Triticum aestivum L.) by means of leaf reflectance measurements Abstract: The ability to identify diseases in an early infection stage and to accurately quantify the severity of infection is crucial in plant disease assessment and management. A greenhouse study was conducted to assess changes in leaf spectral reflectance of wheat plants during infection by powdery mildew and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…It was found that most of the response bands were located in the visible region, and the two spectral ranges at 615-621 nm and 693-696 nm were the most effective to identify PM, YR and NW. This result was consistent with the finding of Graeff et al [41] . As shown in Table 2, six vegetation indexes were selected, including NPCI, ARI, MCARI, TCARI, PhRI and PRI.…”
Section: Identification Of Discrepancies In Spectral Bands and Vegetasupporting
confidence: 94%
“…It was found that most of the response bands were located in the visible region, and the two spectral ranges at 615-621 nm and 693-696 nm were the most effective to identify PM, YR and NW. This result was consistent with the finding of Graeff et al [41] . As shown in Table 2, six vegetation indexes were selected, including NPCI, ARI, MCARI, TCARI, PhRI and PRI.…”
Section: Identification Of Discrepancies In Spectral Bands and Vegetasupporting
confidence: 94%
“…From an economic point of view, the most severe diseases of wheat in the last 5 years in Poland and all of Europe have been: powdery mildew-Blumeria graminis (DC.) Speer [10,22,36,64], brown rust of leaves-Puccinia recondita Rob. Ex Desm f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, the use of conventional digital images to derive green vegetation indices to predict yield and resistance to biotic stresses (caused by pests and diseases) has been reported in recent years (Diéguez-Uribeondo et al, 2003;Graeff et al, 2006;Mirik et al, 2006). Thus the low cost of red, green, blue (RGB) digital cameras makes them an attractive alternative for applications in precision agriculture and/or high-throughput phenotyping (Reyniers et al, 2004;Cabrera-Bosquet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The b component has been claimed to be used for the calculation of the onset of senescence because it measures scalars of the color change that best describes the typical color shifts into yellow that occur during senescence in wheat (Kipp et al, 2014). In that sense, evaluation of plant biomass and the leaf area index in response to the water regime (Casadesús et al, 2007), or the impact of diseases such as brown-spot disease in rice and powdery mildew in wheat (Graeff et al, 2006;Kurniawati et al, 2009) are examples supporting the usefulness of these color traits. However, the applications of digital image analysis by different color bands to evaluate grain yield loss and changes in related physiological traits under rust-infection have not been assayed yet.…”
Section: Introductionmentioning
confidence: 99%